PENGARUH ASIMETRI INFORMASI, KEEFEKTIFAN PENGENDALIAN INTERNAL, KOMITMEN ORGANISASI DAN KOMPETENSI TERHADAP KECENDERUNGAN FRAUD DALAM PENGELOLAAN KEUANGAN DESA DI PEMERINTAH KOTA LHOKSEUMAWE - Nur Afni Yunita; Muhammad Yusra; Rany Gesta Putri Rais (JURNAL EKONOMIKA INDONESIA, 2022)
This research aims to determine the influence of information asymmetry, internal control, organizational commitment, and competence to the tendency of fraud in village financial management in Lhokseumawe City Government. The study used primary data in the form of questionnaires. The data analysis methods used are instrument tests and classical assumption tests as well as multiple linear regression tests using the help of SPSS version 26 software. The results of the partial test obtained that information asymmetry and competence had a positive but insignificant effect on the tendency of fraud in the financial management of the village in Lhokseumawe city government. Meanwhile, internal control has a negative but insignificant effect on the tendency of fraud in the management of village funds in Lhokseumawe city government, while organizational commitment negatively affects the tendency of fraud in village financial management in Lhokseumawe city government.